AI and machine learning - Rahman, Was, 1965- (55 City Road : SAGE Publications Pvt. Ltd, 2020)
Was Rahman's AI and Machine Learning achieves that rare balance of making a difficult and complex topic accessible to non-specialists, without dumbing down. He starts with an enlightening and entertaining explanation of what artificial intelligence (AI) is and how it works. This includes often-overlooked fundamentals like what we actually mean by'intelligence', artificial or otherwise. Rahman brings his explanations to life with lucid and, at times, surprising examples of AI already in use around us. He takes these back to first principles, deftly avoiding any need to understand the maths or computing involved. This allows him to demystify what the technology is really doing and show us that much of it is reassuringly mundane, despite the hype. This distinctive approach comes into its own when examining the challenges and risks of AI. It allows the author to remove the drama and fear of sensationalized headlines and doom-laden movie plots. In their place, he offers an insightful analysis of how the major issues surface, what options we have for addressing them and why some dilemmas may prove intractable. A must-read to understand the reality and implications of AI beyond the hype!
Includes bibliographical references and index.
Description based on XML content.
Keywords: Artificial intelligence